2022
DOI: 10.3390/molecules27092665
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Targets of Resveratrol, a Plant Polyphenol, and Its Role in the Therapy of Various Types of Cancer

Abstract: Cancer is among the most prominent causes of mortality worldwide. Different cancer therapy modes employed, including chemotherapy and radiotherapy, have been reported to be significant in cancer management, but the side effects associated with these treatment strategies are still a health problem. Therefore, alternative anticancer drugs based on medicinal plants or their active compounds have been generating attention because of their less serious side effects. Medicinal plants are an excellent source of phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 204 publications
0
26
0
Order By: Relevance
“…Resveratrol affects a variety of proteins and signaling pathways [ 48 ]. The current study found that this supplementation increases SIRT5 protein levels in the hippocampus of aged rats, supported by another study performed by Gertz et al [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol affects a variety of proteins and signaling pathways [ 48 ]. The current study found that this supplementation increases SIRT5 protein levels in the hippocampus of aged rats, supported by another study performed by Gertz et al [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to various studies, resveratrol is an antioxidant, anti-inflammatory, and anticancer agent [ 25 ]. Because mitochondria play a role in both healthy and diseased states, researchers are also looking into the effect of RES on mitochondrial function and dynamics.…”
Section: Correlation Between Oxidative Stress Antioxidants and Btmentioning
confidence: 99%
“…Resveratrol (RSV, 3,4 ,5-trihydroxystilbene, Figure 1) is a well-known natural polyphenol belonging to the subclass of stilbenoids, which are synthesized by various plants, including peanuts, grapes, and blueberries, in response to physiological or stress stimuli and are present in red wine [1,2]. Many research studies conducted on RSV have demonstrated biological activity in in vitro and in vivo models and have highlighted the potential benefits of this agent for many diseases [3], such as cancer [4,5], cardiovascular disease [6], longevity [7,8], bone health [9,10], neurodegenerative [11], and infectious diseases, including those caused by DNA and RNA viruses [12][13][14][15][16]. RSV efficacy has been related to its ability to modulate several biochemical mediators, as described in many comprehensive review articles on the subject [17,18].…”
Section: Introductionmentioning
confidence: 99%